An inside look at sport psychology consulting - Archer, Mark; Del Padre Visual Productions; Virtual Brands ([Wilbraham, Mass.] : Virtual Brands, 2003)
The video allows viewers to observe the process of applied sport psychology as it unfolds in a series of three individual sessions, highlighting the dynamic interplay of personal and performance issues that can develop over time in sport psychology consulting
Title from title screen
Executive producers, Britt Brewer, Judy Van Raalte, Al Petitpas ; editor, Mark Archer ; camera, Geoff Alson, Mark Archer
Host: Al Petitpas
Consultant: Gloria Balague
Keywords: Sports -- Psychological aspects; Psychological consultation